A netnography and a survey on doping use among competitive doping-untested strength-sport athletes - Jokipalo, I.; Khudayarov, A. (International Journal of Sports Medicine, 2021)
Doping-untested strength-sport athletes (powerlifters, strongmen, armlifters, etc.,) are infamous for their doping use, but their exact doping regimens are not known. The purpose of this study was to provide a reasonable portrait of doping history in this specific athlete group for medical practitioners. Seventy-five athletes were selected by netnography of the social media community around the Finnish doping-untested strength-sport federations on the basis of their activity in doping-related discussions, and the athletes were invited to answer a detailed doping-related anonymous survey. Fifty respondents completed the survey. 100% of the respondents reported use of anabolic androgenic steroids, 66% reported use of stimulants, and 80% use of non-steroidal anabolic substances. The doses of both testosterone products and human growth hormone were notably larger than reported in previous studies of gym users (mostly non-competitive athletes). The subjects reported simultaneous use of an average 5.66 illegal substances, and lifetime use of 16.78 illegal substances. The doses of illicit drugs, as well as polypharmacy, among competitive doping-untested strength-sport athletes are higher than previously reported among recreational gym users, and side effects are likely in this specific population.